Friction and mineral assemblage measurements from IODP subduction zone samples - Matt J Ikari; Achim J Kopf; Andre Hüpers; Christoph Vogt (PANGAEA, 2020)
We combine here the results of laboratory friction experiments and quantification of mineral assemblage for scientific drilling samples recovered from three particularly well-studied subduction zones: the Nankai Trough (SW Japan), Japan Trench (NE Japan), and Costa Rica. The manuscript Ikari et al., 2018 is a compilation of friction and mineral assemblage data for these three sites; reported here are measurements made at the University of Bremen. For this study, we conducted rotary shear tests, measuring the residual friction coefficients for disaggregated samples in a single-direct shear apparatus under effective stresses of 0.6-2.2 MPa and at a shearing rate of 0.3-7.5 μm/s. We also report mineral assemblages for our samples from X-ray diffraction (XRD) analyses.